Biogram księdza Tadeusza Stycznia - RITTER, Cezary (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Tadeusz Styczeń, SDS [Societas Divini Salvatoris], was born on December 21, 1931 in Wołowice, a village near Cracow, Poland. He studied theology on the Theological Faculty at the Jagiellonian University in Cracow and in the Dominican Institute for Philosophy and Theology in Cracow In 1955, he was ordained to the priesthood. He completed his philosophical studies at the Catholic University of Lublin, and specialized in moral philosophy in the Department of Ethics, chaired by Rev. Karol Wojtyła, Ph.D., Honorary Professor of the Catholic University of Lublin. In 1960, Father Styczeń received a Master’s degree in ethics (having presented a Master’s thesis on N. Hartmann’s Concept of Virtue). In 1963, he received a doctoral degree from the Catholic University of Lublin (having presented a dissertation on The Problem of the Possibility of Ethics in John Locke’s Philosophy). In 1963, he was employed in the Department of Ethics at the Catholic University of Lublin, where he continued his research. In 1971, he presented a post−doctoral dissertation (Habilitation) entitled The Problem of a Possibility of Ethics as an Empirically Justified and Universally Valid Theory of Morality. In 1981, he became Assistant Professor at the Catholic University of Lublin and in 1992, he received the title and post of Full Professor. From 1978 to 2002, he held the Chair of Ethics at the Catholic University of Lublin and was Director of the Department of Ethics. From 1982 to 2006 he was Director of the John Paul II Institute at the Catholic University of Lublin and Editor−in−Chief of the quarterly Ethos, both of which he was also the Founder. In 1975, he was Visiting Professor in J. Gutenberg University in Mainz. From 1981 to 1986, he was also Professor in Pontifical John Paul II Institute For Studies on Marriage and Family in Rome. He was Cofounder (in 1981) and Member of the Senate of the International Academy of Philosophy in Dallas, USA (its present location is in the Principality of Liechtenstein and Chile). He was Member of Societas Ethica, Member of the Learned Society of the Catholic University of Lublin, Member of Polish Philosophical Society, Mem− ber of Polish Theological Society. From 1981, he served as Consultor to the Pontifical Council for the Family and from 1985, as Consultor to the Pontifical Council for the Pastoral Care of Health Care Workers. From 1994, he was member of the Pontificial Academy for Life. He was Member of the Research Council of the Institute for the Studies of Family in the Cardinal Stefan Wyszyński University in Warszawa−Łomianki, founded by the late Abp. Kazimierz Majdański. He was Member of the Editorial Board of Roczniki Filozoficzne [“Philosophical Yearly”] He was joint editor of the periodical Aletheia, published by the IAP in Liechtenstein, as well as joint editor of the quarterly Anthropotes, published at the Later− an University in Rome. He cooperated with the journals Il Nuovo Areopago and La Nuova Europa. He was Expert of the Senate Committee for Constitutional Matters. In 1994, he received an honorary doctorate from the University of Navarra in Pamplona, and in 2007, an honorary doctorate from the Lateran University in Rome. Abstracts 422 In 2006, he was awarded the Officer’s Cross of the Order of Polonia Restituta and Austrian Cross of Honour for Science and Art, First Class. In 2007, he received Medal for the Merits for the Catholic University of Lublin. In 2006, Father Styczeń retired from full professorship, but he remained Honorary Director of the John Paul II Institute. He authored over 400 publications, including 20 books. He was also editor of numerous monographic collections, primarily on the thought of John Paul II. Fr. Tadeusz Styczeń died on October 14, 2010, in St. Hedwig Hospital in Trzebnica near Wrocław, after a long illness.